A 3D Multiobject Tracking Algorithm of Point Cloud Based on Deep Learning. (10th December 2020) - Wang, Dengjiang; Huang, Chao; Wang, Yajun; Deng, Yongqiang; Li, Hongqiang
Abstract : 3D multiobject tracking (MOT) is an important part of road condition detection and hazard warning algorithm in roadside systems and autonomous driving systems. There is a tricky problem in 3D MOT that the identity of occluded object switches after it reappears. Given the good performance of the 2D MOT, this paper proposes a 3D MOT algorithm with deep learning based on the multiobject tracking algorithm. Firstly, a 3D object detector was used to obtain oriented 3D bounding boxes from point clouds. Secondly, a 3D Kalman filter was used for state estimation, and reidentification algorithm was used to match feature similarity. Finally, data association was conducted by combining Hungarian algorithm. Experiments show that the proposed method can still match the original trajectory after the occluded object reappears and run at a rate of 59 FPS, which has achieved advanced results in the existing 3D MOT system.